Oxidation of Tyrosine Photoinduced by Pterin in Aqueous Solution - Castaño Espinal, Diana Carolina (2013)
Pterins, heterocyclic compounds widespread in biological systems, accumulate in the skin of patients suffering from vitiligo, a chronic depigmentation disorder. Pterins have been previously identified as good photosensitizers under UV-A irradiation. In this work, we have investigated the ability of pterin (Ptr), the parent compound of oxidized pterins, to photosensitize the oxidation of tyrosine (Tyr) in aqueous solutions. Tyr is an important target in the study of the photodynamic effects of UV-A radiation because it is oxidized by singlet oxygen (1O2) and plays a key role in polymerization and cross-linking of proteins. Steady UV-A irradiation of solutions containing Ptr and Tyr led to the consumption of Tyr and dissolved O2, whereas the Ptr concentration remained unchanged. Concomitantly, hydrogen peroxide (H2O2) was produced. By combining different analytical techniques, we could establish that the mechanism of the photosensitized process involves an electron transfer from Tyr to the triplet excited state of Ptr. Mass spectrometry, chromatography and fluorescence were used to analyze the photoproducts. In particular, oxygenated and dimeric compounds were identified.